Manajemen Pendidikan Madrasah Aliyah di Pondok Pesantren ‘Ibadurrahman Nunukan - Fitriono, Eko Nani; Fouqi Ardatulloh; Anisa; Sephiona; Luluk Rafidah; Samsinar (Rayah Al-Islam, 2025)
This study examines the urgency of effective educational management in the context of globalization and rapid social change, focusing on the case of Madrasah Aliyah Pondok Pesantren Ibadurrahman in Nunukan, Indonesia. This study analyzes the effectiveness of Ibadurrahman's educational management through several key aspects: curriculum planning and implementation, teacher quality, educational facilities and resources, evaluation and feedback mechanisms, and community involvement. Despite challenges such as community perception and teacher qualifications, Ibadurrahman demonstrates a commitment to integrating general and religious education, fostering character development, and providing a supportive learning environment. The research method used in this study is qualitative research, with a field study approach.  The research data is sourced from document and interview data. Data collection techniques were carried out observation, interviews and document analysis. The data analysis technique carried out is a descriptive analysis technique. The study concludes by assessing the contribution of Ibadurrahman's educational model to the success of its graduates in higher education and their contribution to society. The findings highlight the importance of a comprehensive approach to educational management that considers both academic excellence and character development in achieving quality education.